Mengatasi Quarter Life Crisis dan Meningkatkan Potensi Diri Melalui Metode Self-Healing - Pratama, Reza Hardian; Pratama, Muhammad Irfan; Anita, Anita; Afredo, Harold Kevin; Wibowo, Rizki Agung (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The Quarter Life Crisis (QLC) is a phenomenon often experienced by teenagers in their early 20s. It can cause anxiety, confusion, and a sense of loss of direction in life. Therefore, it is important to equip adolescents with knowledge and skills that can help them deal with QLC and increase their potential. The purpose of this community service is to introduce QLC to 11th grade students of SMAN 13 Bandar Lampung and equip them with self-healing methods to increase their potential. The methods used in this activity were lectures, discussions, and self-healing practices. The results showed that after participating in this activity, students had a better understanding of QLC and could identify its signs. In addition, students were also able to apply self-healing methods to increase their potential. In conclusion, this community service activity provided significant benefits for 11th grade students at SMAN 13 Bandar Lampung. Students become more prepared to face QLC and have higher self-confidence to develop their potential.